Perception and tourism development in natural areas: the case of Lake Titicaca - Cayo-Velásquez, Noemí Emperatriz (2019)
The research  aimed to determine the perception and level of knowledge of environmental conservation on the Natural Protected Area of Titicaca Titicaca (NPA); it is of quantitative and descriptive approach, the Delphi method was used and surveys were applied to a panel of 34 experts the results obtained were made through a seven-level Likert scale that have undergone a statistical treatment to test the hypotheses formulated; the first round they reflect that quality management is part of the strategic objectives but is not yet fully integrated, there are problems to perform concrete actions that respond to the needs of visitors; the marketing strategies don´t  respond to promotional actions of the NPA. The second round: the declaration of NPA Lake Titicaca generates conflicts between the steps involved with the local population and doesn´t guarantee its conservation; Planning and regulation actions play a vital role for management, it is stated that with more resources the NPA would achieve its objectives, environmental education produces positive effects, however it isn´t integrated into the planning and management of the NPA.